1970
DOI: 10.3329/jcmcta.v21i1.7666
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Skin Cancer in Chronic Arsenicosis in Chittagong Medical College Hospital

Abstract: Key words: chronic arsenicosis, prevalence; skin cancerDOI: 10.3329/jcmcta.v21i1.7666 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):23-29

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These management measures are found to be helpful in the early recovery of mild and moderate arsenicosis patients. But recovery is difficult in severe arsenicosis cases or in cases with complications 22,4345. In Bangladesh, several studies have been carried out to assess different treatment regimens for arsenicosis patient management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These management measures are found to be helpful in the early recovery of mild and moderate arsenicosis patients. But recovery is difficult in severe arsenicosis cases or in cases with complications 22,4345. In Bangladesh, several studies have been carried out to assess different treatment regimens for arsenicosis patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with spirulina, selenium, or folic acid showed a little improvement. However, vitamin A (β-carotene), E, and C regimen still is a commonly practised management for arsenicosis patients 4346. DGHS supplies vitamin A, E, C to Upazilla Health Complexes for the management of arsenicosis patients, free of cost.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery or improvement was found to have occurred among those who had followed the advice and instructions properly. It has been reported that recovery and improvement was more likely patients with mild or moderate arsenicosis if they consumed arsenic safe water and took antioxidants regularly; however, recovery in patients with severe disease or complications was time taking or even difficult [2,18,19,20,21,22,23]. Though the antioxidants were found to be useful, the mechanism was not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, skin cancers were more common and the types of skin cancers are squamous cell cancer and basal cell cancer. Bowen's disease is a precancerous skin lesion and is evident among the arsenicosis patients of Bangladesh [7,12,74]. It is estimated that there will be a doubling of the potential lifetime mortality risk from cancer in Bangladesh due to arsenic in drinking water and it is indicated that the overall lifetime mortality risk due to cancer of the lung, liver, and bladder resulting from such exposure will be 229.6 per 100,000 population [72].…”
Section: Suspected Case Showing Melanosis or Keratosis After Excludinmentioning
confidence: 99%
“…Mild and moderate arsenicosis cases are found to recover from illnesses using the above management regimen. However, severe arsenicosis cases or cases with complications take longer to recover [1,74,77]. Studies carried out on arsenicosis patient management with different treatment regimens such as spirulina, selenium, and folic acid in Bangladesh found that none of these regimens is very effective [61,77,78], However, the vitamin A, E, and C regimen is still commonly used for arsenicosis management in Bangladesh [74].…”
Section: Management Of Arsenicosis Patients In Bangladeshmentioning
confidence: 99%